Among words, images and indigenisms: Comparative study between Amauta and Titikaka Bulletin - Villanueva Ccahuana, Philarine Stefany (2018)
This paper aims to demonstrate that, in the 1920s, the discourse of in- digenism manifested in cultural journals through its written and visual texts was not homogeneous, but was articulated with other indige- nisms within a complex and heterodox cultural field. Specifically, the aesthetic-ideological proposals of two journals are studied and how they are articulated: Amauta (Lima, 1926-1930) and Titikaka Bulletin (Puno, 1926-1930). It is concluded that the indigenism had a fluc- tuating meaning as it was defined and interpreted in different ways, which were expressed through the written and visual discourse of the publications of this period.